Community Empowerment As a Partner of Local Governmnet In Sustainable Environmental Hygiene Management In Makassar City - Agustang, Andi Dody May Putra; Oruh, Shermina; Agustang, Andi (Seminar Nasional LP2M UNM, 2023)
Abstract. The purpose of this study is to formulate the concept of community empowerment as a partner of local governments in sustainable environmental cleanliness, especially Makassar city waste management. In this section, the concept of community empowerment as a partner of local governments is prepared based on the results of interviews with experts on waste management policies and analyzed using the AHP method. The priority in this study is the pattern of partnership between the city government, the private sector, and the community, as a concept of community empowerment. The second is the implementation of policies and law enforcement, the third is processing with sanitary landfill techniques and the fourth is the improvement of facilities and infrastructure. Keywords: priorities, strategies and policies, community empowerment, AHP